Mazhab Feminisme dan Pengaruhnya di Indonesia - Pahlevi, Andika Tegar; Zulaiha, Eni; Huriani, Yeni (Definisi: Jurnal Agama dan Sosial Humaniora, 2022)
This paper aims to explain things about the Feminist School and also the emergence of the Feminism movement and some issues that are developing in Indonesia. This research method uses library research referring to qualitative data in the form of writings and books that the author has examined. Based on the results of the reading that the author obtained, namely, that the school of feminism is a stream that is formed within feminism itself. There are many streams of feminism that were born, including liberal feminism, radical feminism and Marxist feminism and socialist feminism. After the emergence of these schools, Feminism also gave birth to various movements that emerged in protecting and fighting for the rights and dignity of women. The feminist movement initially aimed to end and end the status of deprivation of women's freedom. One of the movements is the women's march which is very relevant in fighting for women.